2010
DOI: 10.1007/s00395-010-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of cGMP-PKG signaling in the protection of neonatal rat cardiac myocytes subjected to simulated ischemia/reoxygenation

Abstract: Nitric oxide (NO) and B-type natriuretic peptide (BNP) are protective against ischemia-reperfusion injury as they increase intracellular cGMP level via activation of soluble (sGC) or particulate guanylate cyclases (pGC), respectively. The aim of the present study was to examine if the cGMP-elevating mediators, NO and BNP, share a common downstream signaling pathway via cGMP-dependent protein kinase (PKG) in cardiac cytoprotection. Neonatal rat cardiac myocytes in vitro were subjected to 2.5 h simulated ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 39 publications
2
73
1
Order By: Relevance
“…These effects are accompanied by an increased PKG activity and attenuated by PKG inhibitors or by selective knockdown of PKG in cardiomyocytes (Das, 2008 et al;Gorbe et al, 2010). It is generally recognized that ischemia/reperfusion injury arises primarily from the opening of the mitochondrial permeability transition pore (mPTP) in the first minutes of reperfusion.…”
Section: Cardioprotective Action Against Ischemia-reperfusion Injurymentioning
confidence: 99%
“…These effects are accompanied by an increased PKG activity and attenuated by PKG inhibitors or by selective knockdown of PKG in cardiomyocytes (Das, 2008 et al;Gorbe et al, 2010). It is generally recognized that ischemia/reperfusion injury arises primarily from the opening of the mitochondrial permeability transition pore (mPTP) in the first minutes of reperfusion.…”
Section: Cardioprotective Action Against Ischemia-reperfusion Injurymentioning
confidence: 99%
“…We have previously shown that the exogenously administered NO donor S-nitroso-nacetyl-penicillamine (SNAP) and the particulate guanylate cyclase activator B-type natriuretic peptide (BNP) exert cytoprotective effect against simulated ischemia/reoxygenation (SI/R) injury in primary neonatal rat cardiomyocytes [58]. This protection acts via the activation of cGMP/PKG signaling pathway, thereby stimulating its multiple downstream signal transduction cascade which leads to increased cell viability against SI/R injury [59,58,60].…”
Section: +mentioning
confidence: 99%
“…This protection acts via the activation of cGMP/PKG signaling pathway, thereby stimulating its multiple downstream signal transduction cascade which leads to increased cell viability against SI/R injury [59,58,60].…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations